Analysis of urinary estrogens, their oxidized metabolites and other endogenous steroids by benchtop orbitrap LCMS versus traditional quadrupole GCMS - Franke, Adrian A. (2011)
Estrogens and other endogenous steroids are known risk markers for cancer. Gas chromatography (GC) with mass spectrometry (MS) has traditionally predominated the analysis of estrogens and other endogenous steroids but liquid chromatography (LC) MS is increasingly favored. Direct comparisons of the two technologies have hitherto not been performed. Steroids were analyzed in urine from 232 premenopausal women in a blinded fashion by benchtop orbitrap LCMS and single quadrupole GCMS. 16 steroidal estrogens including oxidized metabolites could be analyzed by LCMS. LCMS-GCMS Spearman rank correlations of the major estrogens E(1), E(2), E(3), 16α-OHE(1), and 2-OHE(1) were very high (r=0.72–0.91), and absolute concentrations also agreed (<5% difference for E(1), E(2), E(3), 16α-OHE(1)). LCMS allowed reinterrogation of acquired data due to orbitrap technology, which permitted post-analysis quantitation of progesterone, cortisol, and cortisone (LCMS-GCMS Spearman rank correlations=0.80–0.84; absolute difference <7%; n=137). GCMS allows the measurement of a wide range of steroids including non-polar analytes that escape the presented LCMS assay. In contrast, orbitrap based LCMS can detect more estrogens, is faster, less costly, allows post data acquisition reinterrogation of certain analytes that had not been targeted a priori, and requires much less urine.